A comparative study of ionospheric profile parameters B0 and B1 over Chumphon with IRI-2012 - Jamjareegulgarn, Punyawi; Supnithi, Pornchai; Wichaipanich, Noraset; Ishii, Mamoru; Maruyama, Takashi (My University, 2015)
Average diurnal variations of ionospheric profile parameters B0 and B1 in 2009 are studied over Chumphon province, Thailand, and compared those variations with IRI-2012 model. The thickness parameter (B0) and the shape parameter (B1) are two main parameters to compute and depict the F2-layer electron density profile. IRI-2012, the latest version of IRI model, offers three options to provide B0 and B1, i.e., Bil-2000, Gul-1987, ABT-2009. Those options have never been taken for studying and comparing with the ionospheric observation data from a FM/CW ionosonde, Chumphon. Moreover, the observed B0 and B1 from Thailand have never been analyzed nor used while establishing the new table of (B0, B1) values of the IRI model. Hence, B0 and B1 observation is necessary as a part of the global validation study of the IRI-2012 model. Our studies show that: (1) In general, the average diurnal variations of B0 for the observation and the IRI-2012 model show the same trends, except B0 of Gul-1987 during 20:00 - 02:00 LT. The observed B0 averages are equal to 166.13 km and 99.18 km in the daytime and nighttime, respectively. (2) The average diurnal variations of B1 for the observation and the IRI-2012 model show the same trends, except B1 of ABT-2009. Average diurnal variations of the observed B1 look like a sine wave where the peak and lowest values can be found around the midnight and the noontime, respectively. For the IRI-2012 model, B1 of Gul-1987 is the same value as B1 of Bil-2000. The observed B1 averages are equal to 1.98 and 2.51 in the daytime and nighttime, respectively. Our observed B0 and B1 results are similar to other studies in equatorial latitude and low latitude stations. Our comparative studies provide some details for improving B0 and B1 parameters of CCIR-based IRI model in the equatorial latitude region.
Keywords: B0; B1; CCIR; Chumphon; equatorial latitude; IRI-2012; NeQuick version 2